Recent advances in understanding propeller jet flow and its impact on scour - Wei, Maoxing (2021)
This paper presents an extensive review of the characteristics of a propeller jet-induced flow field and its impact on scour formation. As the driving force of scour, the jet flow behavior is first explored, including both the free and bounded jets under various boundary conditions. Accordingly, their resulting scour, namely, unconfined and confined scour, are expounded in terms of the temporal and spatial development of the scour depth. Hitherto, existing methods for predicting the scour depth are principally developed empirically, which exclude in-depth scrutiny into the mechanism governing the scouring process. With the detailed flow fields obtained in recent research, this paper aims to piece together a state-of-the-art understanding of the scouring mechanism governing confined propeller scour, that is, the combined effect of jet flow and junction flow on the scour hole development. By comparing the similarities and differences between the scouring mechanisms in open and closed quays, this paper provides a comprehensive insight into the scouring process associated with bounded propeller jets. Moreover, in terms of the near-bed flow variations during the scouring process, implications for sediment transport under highly turbulent flow are discussed. Finally, future research needs are identified.